Comparison of conventional temporalis fascia myringoplasty with fascia lata myringoplasty among patients with hearing loss - Verma, Sumeer; Arora, Anshu; Narvey, Ved Prakash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: In selection of a graft tissue factors considered include its biological properties, probability of survival, its adequacy in size and ease of procurement The present study aims to preoperatively predict hearing improvement by paper patch test and compare with postoperative hearing improvement i.e. pre and post operatively hearing assessment. Methods: The study was conducted on 25 cases undergoing myringoplasty with Fascia lata and Temporalis fascia as a graft material among the patients fulfilling the standard criteria for myringoplasty i.e. pars tensa perforation, good cochlear reserve, dry ear and normal eustachian tube function were considered for surgery. Myringoplasty was done from post aural route for harvesting fascia temporalis graft & from upper 1/3rd of thigh laterally to harvest fascia lata. Each case was followed up post operatively monthly for 3 months. Results: Factors which influence graft take up are the size of perforation and lack of infection at the time of surgery and postoperative. Large perforations were difficult to repair as it took more time to heal. Surgery performed postaurally underlay technique using temporal fascia was associated with less morbidity, better uptake and lesser postoperative complications but permeatal route also serve similar purpose and does not affect the result of study significantly. Conclusions: This study compared both temporal fascia and fascia lata as graft materials for myringoplasty and proved that myringoplasty done by postaural underlay technique using temporal fascia holds best as per graft uptake, hearing improvement and postoperative complications when compared to fascia lata myringoplasty.